The Baduy Tribe's Political Participation in Indonesia's Democratic Framework - I Nyoman Nurjaya; Navisa, Fitria Dewi; La Ode Machdani Afala (Faculty of Law, Universitas Brawijaya, 2025)
This research investigates the phenomenon of political participation among the tribal community of the Baduy Tribe within the context of general elections (Pemilu) in Lebak Regency, Banten, Indonesia. An in-depth understanding of the political dynamics of the Baduy Tribe is urgently needed to ensure their democratic rights and promote greater involvement in the national political process. This study identifies structural and cultural barriers hindering Baduy's political engagement and proposes practical strategies to overcome these obstacles. The findings are expected to provide valuable insights for policymakers and stakeholders in efforts to strengthen the political representation of the Baduy Tribe. This research employs an empirical approach combining legal and political analysis. Data collection techniques involve in-depth interviews with members of the Baduy tribal community and traditional leaders (pu’un), participatory observation, and analysis of policy-related documents and regulations. The research findings indicate that dynamics between traditional customs, local economy, and national politics influence the political participation of the Baduy community. Despite their high commitment to the democratic process, they face constraints such as administrative requirements and incongruence between customary and formal rules. In conclusion, recognizing their local identity, protecting political rights, and meeting the needs of public services are the primary focus of enhancing inclusive political participation for the Baduy community.